Hukum Islam : dinamika dan perkembangannya di Indonesia - Anshori, Abdul Ghofur; Harahab, Yulkarnain, 1970- (Yogyakarta : Kreasi Total Media, 2008)
Development and implementation of Islamic law in Indonesia.
Includes bibliographical references (pages 307-314) and index.
Keywords: Islamic law -- History -- Indonesia